179k views
3 votes
2x^2=4+6x
Show your work please

User Royalghost
by
6.0k points

1 Answer

3 votes

Answer: x = 3 - sqrt 17 / 2 , x = 3 + sqrt 17 / 2

Step-by-step explanation:

2x^2 = 4 + 6x

divide both sides by 2

x^2 = 2 + 3x

move expression to the left

x^2 - 2 - 3x = 0

reorder the terms

x^2 - 3x - 2 = 0

use the quadratic formula

x = - (-3) +- sqrt (-3)^2 - 4 x (-2) / 2 x 1

calculate

x = 3 +- sqrt 17 / 2

answer

x = 3 - sqrt 17 / 2 , x = 3 + sqrt 17 / 2

User Ray Koren
by
5.8k points